The Activity of Cainito Leaves Ethanol Extract (Chrysophyllum cainito L.) on Wistar’s Total Erythrocites Induced Cyclophosphamide - Heri Puguh Widodo; Ika Rahmawati Sutejo; Rini Riyanti (Faculty of Medicine, University of Jember, 2020)
One of the commonly used chemotherapy drugs is cyclophosphamide. However, the use of cyclophosphamide can provide various toxic effects. The most common toxic effect of cyclophosphamide is bone marrow suppression with anemia as one of its markers. The antioxidant content of cainito leaf potentially increase the production of blood cells, especially erythrocytes. The aims of this study is determining the effectiveness of the cainito leaf ethanol extract against cyclophosphamide induced mouse erythrocyte count in vivo. A sample of 20 male wistar rats was divided into five groups; normal group, negative control group, and three groups of ethanol extract of cainito leaf with dose 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW were administered for one week followed by intraperitoneal cyclophosphamide with dose 50 mg/kgBW as much as one time. One Way Anova Test result showed a significance of 0.015 (p<0.05). However, the LSD test results showed no significant different results between the negative control group and the treatment group. The conclusion was that there was no difference in the amount of erythrocytes in mice given only cyclophosphamide with previous rats given cainito extract.